Money as Justice: The Case of Bosnia and Herzegovina - Alma Begicevic (Oñati Socio-Legal Series)
If reparations are universally accepted as a victims’ right to remedy, included in numerous international law instruments, why is it then that victims are unable to access it? By taking a socio-legal approach to the problem of post-war monetary reparation, the study examines the nexus between money, justice and recognition. At a normative level the study examines how reparations are conceptualized and their meaning in post-conflict transition. At a procedural level it identifies obstacles and gaps in the national, regional and international legal architecture and at an empirical level it investigates people’s experiences in regards to accessing monetary reparations. The study considers the meaning of money in post-war reparation and state transformative processes and significance of civil law in addressing serious violations of human rights and gross violations of humanitarian law.